Analisis Angin Permukaan Menggunakan Diagram Wind Rose untuk Keselamatan Penerbangan di Bandara Internasional Juwata - Gede Yamuna Ceswaraningrat, Ida Bagus; Aryashta, Danurahni; Hermansyah, Muhammad (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2024)
Weather is one of the main factors that can affect flight performance and safety, where wind is an important parameter because it accounts for at least 10% of the total number of aircraft accidents that occur. To minimize this potential, this study was conducted to know the wind patterns that occurred throughout 2015 to 2023, the monthly wind patterns, the wind patterns in 6-hour intervals, and identifying periods with wind speeds = 10 knots. Juwata Tarakan International Airport was chosen as the location of this study by utilizing wind direction and speed data obtained from hourly METAR data by BMKG Tarakan. The analysis used quantitative methods presented in the form of wind rose diagrams and tables. The results showed that the airport is safe in carrying out take-off and landing operations for various types of aircraft, as evidenced by the percentage of wind speed frequency 10 knots each month reaching 98%. However, airline pilots need to be aware of crosswinds with wind speeds = 10 knots which have the potential to be quite large from July to September. The dominant wind direction in the early morning was calms and followed by the North, in the morning was calms and followed by the Northwest, in the afternoon was blowing from the East, then in the evening was calms and followed by the East. The dominant wind speed that blew throughout the day from early morning to night was in the range of 2 - 7 knots.